QRIS Adoption Intention for MSMEs in Indonesia: Integration of Technology Acceptance Model (TAM) and Theory of Planned Behavior (TPB) to Accelerate Digital Transformation - Wahdiniawati, Siti Annisa; Randyantini, Vely; Apriani, Ari; Saputri, Ika Puji (Dinasti International Journal of Economics, Finance & Accounting, 2026)
The urgency of this research is to be carried out considering the low adoption of QRIS among MSMEs in Indonesia (only 46.4% of 65 million MSMEs), even though QRIS offers cost efficiency, market expansion, and transaction transparency. This low penetration has the potential to hamper the financial inclusion and competitiveness targets of MSMEs in the 2024 Digital Indonesia roadmap. The purpose of the study was to analyze the dominant factors of QRIS adoption intention through the integration of Technology Acceptance Model (TAM) and Theory of Planned Behavior (TPB), combining psychological variables (attitude), technological perception (perceived ease of use, perceived usefulness), social factors (subjective norm), and perceived behavioral control. The method used is mixed methods by distributing questionnaires to MSMEs that have not yet adopted QRIS in Greater Jakarta (PLS analysis) and in-depth interviews with 7 MSME actors to uncover structural (infrastructure, digital literacy) and cultural barriers (non-cash transaction resistance). The sample of this study is 140 business actors who have not used QRIS. The results of the interview concluded that perceived cost is an obstacle for MSME actors not to use QRIS, then it is lowered to a research variable and included in the research model. The findings of this study are that perceived ease of use and perceived usefulness have a positive and significant effect on attitude, perceived cost, attitude, perceived behavioral control have a positive and significant effect on intention to use, while subjective norms have no effect on intention to use. Furthermore, attitude can mediate the influence of perceived ease of use and perceived usefulness on intention to use.